PARTITIONING OF TRACE AMOUNTS OF HIGHLY SIDEROPHILE ELEMENTS IN THE FE-NI-S SYSTEM AND THEIR FRACTIONATION IN NATURE - EVIDENCE FOR CORE-MANTLE INTERACTION? - Fleet M.E.; Liu M.; Crocket J.H. (My University, 1999)
The partitioning of highly siderophile elements (HSEs: Re, Os, Ir, Pt, Pd, and Au) between solid metal and liquid metal sulfide in the Fe-Ni-S system at 1000 to 1200°C and low pressure has been investigated at abundances close to those in nature by using neutron activation analysis. Partition coefficients (D) are high for the most refractory metals (Re, Os, and Ir), intermediate for Ru and Pt, and near unity for the least refractory metals (Pd, Ni, and Au), results broadly consistent with literature data. The partitioning of HSE seems to be reasonably independent of the concentration of these elements (trace to minor), temperature (1000 to 1900°C), and pressure (1 bar to 11 GPa), but varies markedly with variation in bulk composition, particularly for the refractory metals. We demonstrate fractionation of Re and Os in the Fe-S system [molar D(Os)/D(Re) = 1.15 +/- 0.11] consistent with fractionation patterns for Re and Os in magmatic iron meteorites and qualitatively consistent with that hypothesised for 187Os-enrichment in some oceanic island basalt (OIB) sources. Laboratory partition coefficients for HSE in the Fe-Ni-S system correlate closely with log HSE vs. log Ni regression slopes of the magmatic iron meteorites. The selective partitioning behavior of HSE is related to the extreme range in melting point of the pure elements, and is unlikely to be erased completely by pressures in the earth's core, even in the hypothetical absence of S. Also, the abundances of HSE in mantle peridotites and OIB could not have been influenced by partitioning between large quantities of solid metal and liquid metal sulfide.